MoS2 and Perylene Derivative Based Type‐II Heterostructure: Bandgap Engineering and Giant Photoluminescence Enhancement. Issue 3 (12th December 2019) - Obaidulla, Sk Md; Habib, Mohammad Rezwan; Khan, Yahya; Kong, Yuhan; Liang, Tao; Xu, Mingsheng
Abstract: 2D transition metal dichalcogenides (TMDs) are a promising material system for optoelectronic applications. However, their key figure of merit, the room‐temperature photoluminescence (PL), is extremely low. To overcome this challenge, TMDs need interfacing with other semiconducting materials and discover the underlying physical phenomena. Herein, the optical properties and PL mechanisms of molybdenum disulfide‐organic perylene derivative (PDI/MoS2 ) based type‐II heterostructures, i.e., PTCDA/MoS2 and PTCDI‐Ph/MoS2, are studied experimentally and theoretically. The PL of MoS2 in PTCDA/MoS2 is enhanced, while a dramatic PL quenching of MoS2 is observed on PTCDI‐Ph/MoS2 . The significant radiative PL enhancement of PTCDA/MoS2 is primarily due to the bandgap reduction, high exciton/trion ratio, and epitaxial growth of PTCDA. In contrast, "trap‐like" states in heterointerface, relatively low exciton/trion ratio, and less ordered morphology are responsible for PL quenching of PTCDI‐Ph/MoS2 heterostructure. These findings would provoke a new way to engineer the light‐matter interactions in organic/TMD hybrids, which enables light‐emitting, light‐harvesting applications, and neuromorphic devices. Abstract : The contrasting photoluminescence (PL) emission behavior of molybdenum disulfide‐organic perylene derivative (PDI/MoS2 ) based type‐II heterostructures—PTCDA/MoS2 and PTCDI‐Ph/MoS2 —is explored. The significant PL enhancement is exhibited in PTCDA/MoS2 while PL quenching is observed in PTCDI‐Ph/MoS2 . The intense PL emission of PTCDA/MoS2 is due to reduced bandgap, large exciton/trion ratio, and ordered morphology of PTCDA. In contrast, formation of "trap‐like" states, relatively low exciton/trion ratio, and less ordered morphology are responsible for PL quenching of PTCDI‐Ph/MoS2 heterostructure.